Just rewards - Bradford, Barbara Taylor, 1933- (Bradford, Barbara Taylor, 1933- Emma Harte saga., 2006)
Just Rewards is the dramatic conclusion of the extraordinary tale of Emma Harte's great granddaughters. In this sweeping novel, the Harte women find themselves in the midst of weddings and intrigue. Linnet O'Neill, great-granddaughter of Emma Harte, finds herself following in the footsteps of the original woman-of-substance as she battles to modernize the family business. Returning from her honeymoon full of fresh ideas for bringing the Harte empire into the new century, Linnet locks horns with her mother, Paula, in a battle about the future. But when Paula falls ill, Linnet finds herself alone at the helm, just as her great-grandmother once was. Evan Hughes, Linnet's American cousin, is pregnant and planning her small family wedding. Life seems good until a harsh confrontation with her adopted sister puts Evan in the hospital. Tessa Fairley, Linnet's sister, is ready to start a new life after an acrimonious divorce, which might include rivaling Linnet for the top spot in the Harte business. In the midst of planning her own glamorous summer wedding in Ireland, India Standish is thrown off balance when her fiancé's daughter Atlanta comes to live with them<U+2014>closely followed by his unstable ex-girlfriend, intent on trouble. However, it is Evan's sister Angharad who makes the most ripples within the family, trying to infiltrate the quartet of young women and latching on to Jonathan Ainsley, the deadly enemy of the Hartes, endangering every family member in the process.